Islamic Education in The Digital Era: Overcoming Barriers and Maximizing Opportunities - Muhtar, Fathurrahman; Manan, Abdul Latif (Al Ulya: Jurnal Pendidikan Islam, 2025)
This article examines the impact of digital transformation and scientific development on Islamic thought, education, and society. It explores how the stagnation of rational inquiry following the post-Ibn Rushd era, compounded by the closure of ijtihad and the dominance of dogmatic interpretations, has weakened the intellectual capacity of Muslims to respond to contemporary global challenges. Drawing from theories of scientific paradigm shifts (Kuhn), future shock (Toffler), and knowledge society (Kumar), the study argues that Islamic education must adapt by integrating digital technologies, reformulating epistemology, and reviving the Islamization of science. It highlights both opportunities and threats in the digital era, including the rise of online da'wah and virtual Islamic learning, as well as the misuse of digital media for radicalism and pornography. The paper concludes that reimagining Islamic knowledge systems—through critical, ethical, and innovative engagement with digital tools—is essential to ensure Islam’s relevance in the 21st century. Strategic recommendations are offered to realign Islamic education with the demands of the digital age, while preserving its core spiritual values.